The Grammar of Obviousness: The Palm-Up Gesture in Argument Sequences - Marrese, Olivia H.; Raymond, Chase Wesley; Fox, Barbara A.; Ford, Cecilia E.; Pielke, Megan (Frontiers in Communication, 2021)
This paper investigates the body’s role in grammar in argument sequences. Drawing from a database of public disputes on language use, we document the work of the palm-up gesture in action formation. Using conversation analysis and interactional linguistics, we show how this gesture is an interactional resource that indexes a particular epistemic stance—namely to cast the proposition being advanced as obvious. In this report, we focus on instances in which participants reach what we refer to as an ‘impasse’, at which point the palm up gesture becomes a resource for reasserting and pursuing a prior position, now laminated with an embodied claim of ‘obviousness’ that is grounded in the sequentiality of the interaction. As we show, the palm up gesture appears with and in response to a variety of syntactic and grammatical structures, and moreover can also function with no accompanying verbal utterance at all. This empirical observation challenges the assumption that a focus on grammar-in-interaction should begin with, or otherwise be examined in relation to, ‘standard’ verbal-only grammatical categories (e.g., imperative, declarative). We conclude by considering the gestural practice we focus on alongside verbal grammatical resources (specifically, particles) from typologically distinct languages, which we offer as a contribution to ongoing discussions regarding an embodied conceptualization of grammar—in this case, epistemicity.